A genealogy of critique: From parrhesia to prophecy. (August 2017) - Boland, Tom; Clogher, Paul
This article addresses contemporary concerns about critique through an interpretation of the "writing prophets." This approach draws on Foucauldian genealogy and suggests that alongside Greek parrhesia, Old Testament prophecy is a key forerunner of contemporary critical discourses. Our analysis draws upon Weber's interpretative historical sociology and Gadamerian hermeneutics but shifts the emphasis from charisma to critique, through a direct engagement with prophetic texts. In particular, prophetic discourse claims to reveal injustice and idolatry and speaks from a position of transcendence within immanent historical moments. Prophets position their own era as a moment of crisis, and themselves as liminal figures, opposed to the delusion of others and "false prophets" which resonates with contemporary conceptions of "ideology." Rather than focusing on historical individuals, we approach prophecy as a discourse, multiple and hybrid, discontinuous, and contradictory, yet constituting a distinctive precursor which informs contemporary critique.